O Canto da Cigarra: A poesia cósmica e existencialista de Valdelice Pinheiro. - Moreira, Naynara Tavares (2008)
The present paper objective to make an critical exegesis on Valdelice Soares Pinheiro´s works starting on her published works: "From within of me"(De dentro de mim - 1961), "Pact" (Pacto - 1977) and "The Poetical Expression of Valdelice Pinheiro" (Expressão Poética de Valdelice Pinheiro - 2002). In order to reach this purpose, it looks for recognizing some aspects which allow her insertion on modern poetry and the uniqueness in which she shows the tribulations of contemporary men. The proposal starts on contextualizing the poet and her works on Bahia and Brazil´s poetry scene, emphasizing the women, trying, then, to understand the development of Pinheiro´s poetical writings upon the interpretative readings of the poems on each book. At last, it makes an deeper analysis of the content, focusing the cosmic and existentialist themes, setting talks between Jean-Paul Sarte, Albert Camus, Dostoievsky, Milan Kundera and Marcel Proust, bases for comprehension of the usual themes of her: the absurd of human condition, freedom, writings and the concern about being and be in the universe. Such questions demands the discussion on the position of poetry on contemporaneity and the identification of Pinheiro´s essentialist and spiritualist poetry collating it with other samples of such poetry, both nearby and far from the poet.